Requirement for YAP1 signaling in myxoid liposarcoma. Issue 5 (21st March 2019) - Trautmann, Marcel; Cheng, Ya‐Yun; Jensen, Patrizia; Azoitei, Ninel; Brunner, Ines; Hüllein, Jennifer; Slabicki, Mikolaj; Isfort, Ilka; Cyra, Magdalene; Berthold, Ruth; Wardelmann, Eva; Huss, Sebastian; et al.
Abstract: Myxoid liposarcomas (MLS), malignant tumors of adipocyte origin, are driven by the FUS‐DDIT3 fusion gene encoding an aberrant transcription factor. The mechanisms whereby FUS‐DDIT3 mediates sarcomagenesis are incompletely understood, and strategies to selectively target MLS cells remain elusive. Here we show, using an unbiased functional genomic approach, that FUS‐DDIT3‐expressing mesenchymal stem cells and MLS cell lines are dependent on YAP1, a transcriptional co‐activator and central effector of the Hippo pathway involved in tissue growth and tumorigenesis, and that increased YAP1 activity is a hallmark of human MLS. Mechanistically, FUS‐DDIT3 promotes YAP1 expression, nuclear localization, and transcriptional activity and physically associates with YAP1 in the nucleus of MLS cells. Pharmacologic inhibition of YAP1 activity impairs the growth of MLS cells in vitro and in vivo . These findings identify overactive YAP1 signaling as unifying feature of MLS development that could represent a novel target for therapeutic intervention. Synopsis: The transcriptional co‐activator YAP1 is essential in myxoid liposarcoma (MLS), an aggressive soft‐tissue tumor. This study reveals a link between aberrant YAP1 signaling and the FUS DDIT3 fusion oncoprotein that drives MLS. Pharmacologic YAP1 inhibition impairs MLS growth in vitro and in vivo . YAP1, encoding a transcriptional co activator that is inhibited by the Hippo pathway, was identified by RNA interference screening as an essential gene in mesenchymal stem cells expressing FUS‐DDIT3. FUS‐DDIT3‐expressing MLS cell lines and MLS patient specimens exhibited increased YAP1 activity, and YAP1 suppression in MLS cells caused proliferation arrest, senescence, and apoptosis. FUS DDIT3 induced the expression and nuclear localization of YAP1 and its downstream effectors. FUS‐DDIT3 and YAP1 physically associated in the nucleus of MLS cells. MLS cells were sensitive to pharmacologic blockade of YAP1 activity. Abstract : The transcriptional co‐activator YAP1 is essential in myxoid liposarcoma (MLS), an aggressive soft‐tissue tumor. This study reveals a link between aberrant YAP1 signaling and the FUS DDIT3 fusion oncoprotein that drives MLS. Pharmacologic YAP1 inhibition impairs MLS growth in vitro and in vivo .